Amplification‐Free Detection of SARS‐CoV‐2 and Respiratory Syncytial Virus Using CRISPR Cas13a and Graphene Field‐Effect Transistors. Issue 32 (31st May 2022) - Li, Huijie; Yang, Jie; Wu, Guangfu; Weng, Zhengyan; Song, Yang; Zhang, Yuxuan; Vanegas, Jeffrey A.; Avery, Lori; Gao, Zan; Sun, He; Chen, Yupeng; Dieckhaus, Kevin D.; et al.
Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated (Cas) systems have recently received notable attention for their applications in nucleic acid detection. Despite many attempts, the majority of current CRISPR‐based biosensors in infectious respiratory disease diagnostic applications still require target preamplifications. This study reports a new biosensor for amplification‐free nucleic acid detection via harnessing the trans‐cleavage mechanism of Cas13a and ultrasensitive graphene field‐effect transistors (gFETs). CRISPR Cas13a‐gFET achieves the detection of SARS‐CoV‐2 and respiratory syncytial virus (RSV) genome down to 1 attomolar without target preamplifications. Additionally, we validate the detection performance using clinical SARS‐CoV‐2 samples, including those with low viral loads (Ct value >30). Overall, these findings establish our CRISPR Cas13a‐gFET among the most sensitive amplification‐free nucleic acid diagnostic platforms to date. Abstract : CRISPR Cas13a‐gFET biosensors are reported for target amplification‐free and ultrasensitive detection of SARS‐CoV‐2 and respiratory syncytial virus. The sensor harnesses the trans‐cleavage mechanism of Cas13a and the high sensitivity of graphene field‐effect transistors (gFETs). The sensor performance was validated using synthetic targets, heat‐inactivated virus samples, and clinical samples, showing a sensitivity comparable to that of RT‐qPCR.